SANE-A-PALOOZA: Logistical Development and Implementation of a Clinical Immersion Course for Sexual Assault Nurse Examiners. Issue 4 (October 2016) - Baker, Jodi; Kelly, Patricia J.; Carlson, Kimberly; Colbert, Sharon; Cordle, Carolyn; Witt, Jacki S.
Abstract : ABSTRACT: SANE-A-PALOOZA, a continuing education program that utilizes hands-on practice with standardized patients and human simulators, was developed to fulfill a portion of the required supervised clinical experience for certification as a sexual assault nurse examiner. The program is designed to provide concentrated clinical skill practice application, eliminate the time gap between gaining and applying clinical knowledge, and decrease discontinuity among multiple preceptors. This article provides an overview of SANE-A-PALOOZA logistics, with the goal of aiding other organizations in developing skill-building experiences for new or less-experienced sexual assault nurse examiners. Abstract : Supplemental digital content is available in the text.